The Physiological Impact of Masking Is Insignificant and Should Not Preclude Routine Use During Daily Activities, Exercise, and Rehabilitation. Issue 1 (January 2021) - Haraf, Rebecca H.; Faghy, Mark A.; Carlin, Brian; Josephson, Richard A.
Abstract : Purpose: Masking has been employed as a strategy for reducing transmission of a variety of communicable diseases. With the outbreak of SARS-CoV-2, many countries have implemented mandatory public masking. However, the perceived impact of mask use on pulmonary function has been a deterrent to public compliance with recommendations. COVID-19 has shed light on the impact that comorbid cardiac and pulmonary conditions may have on disease severity. This knowledge has led to increased primary and secondary prevention efforts for which exercise and rehabilitation are central. The importance of safe methods of exercise while mitigating risk of viral transmission is paramount to global recovery from the pandemic and prevention of future outbreaks. Methods: We constructed a focused literature review of the impact of various masks on pulmonary function at rest and with exercise. This was then incorporated into recommendations for the integration of masks with exercise and rehabilitation in the COVID-19 era. Results: While there is a paucity of evidence, we identified the physiological effects of masking at rest and during exercise to be negligible. The perceived impact appears to be far greater than the measured impact, and increased frequency of mask use leads to a physiological and psychological adaptive response. Conclusions: Masking during daily activities, exercise, and rehabilitation is safe in both healthy individuals and those with underlying cardiopulmonary disease. Rehabilitation participants should be reassured that the benefits of masking during COVID-19 far outweigh the risks, and increased frequency of mask use invokes adaptive responses that make long-term masking tolerable. Abstract : With the outbreak of SARS-CoV-2, mandatory public masking has been broadly implemented. However, the perceived impact of mask use on pulmonary function is a deterrent to public compliance. In this report, we review the impact of masks on pulmonary function and provide recommendations for masking during exercise and rehabilitation during COVID-19.